Itch and autophagy-mediated NF-κB activation contributes to inhibition of cathepsin D-induced sensitizing effect on anticancer drugs - Seung Un Seo; Seon Min Woo; Kyoung-jin Min; Taeg Kyu Kwon (Cell Death and Disease, 2022)
Abstract Inhibition of cathepsin D (Cat D) sensitizes cancer cells to anticancer drugs via RNF183-mediated downregulation of Bcl-xL expression. Although NF-κB activation is involved in the upregulation of RNF183 expression, the molecular mechanism of NF-κB activation by Cat D inhibition is unknown. We conducted this study to investigate the molecular mechanism underlying Cat D-mediated NF-κB activation. Interestingly, Cat D inhibition-induced IκB degradation in an autophagy-dependent manner. Knockdown of autophagy-related genes (ATG7 and Beclin1) and lysosome inhibitors (chloroquine and bafilomycin A1) blocked IκB degradation via Cat D inhibition. Itch induced K63-linked ubiquitination of IκB and then modulated the protein stability of IκB by Cat D inhibition. Inhibition of Cat D-mediated Itch activation was modulated by the JNK signaling pathway, and phosphorylated Itch could bind to IκB, resulting in polyubiquitination of IκB. Additionally, inhibition of Cat D increased autophagy flux via activation of the LKB1-AMPK-ULK1 pathway. Therefore, our results suggested that Cat D inhibition activated NF-κB signaling via degradation of autophagy-dependent IκB, which is associated with the upregulation of RNF183, an E3 ligase of Bcl-xL. Cat D inhibition enhances TRAIL-induced apoptosis through Bcl-xL degradation via upregulation of RNF183.